CineCT platform for in vivo and ex vivo measurement of 3D high resolution Lagrangian strains in the left ventricle following myocardial infarction and intramyocardial delivery of theranostic hydrogel. (May 2022) - Midgett, D.E.; Thorn, S.L.; Ahn, S.S.; Uman, S.; Avendano, R.; Melvinsdottir, I.; Lysyy, T.; Kim, J.S.; Duncan, J.S.; Humphrey, J.D.; Papademetris, X.; Burdick, J.A.; et al.
Abstract: Myocardial infarction (MI) produces acute changes in strain and stiffness within the infarct that can affect remote areas of the left ventricle (LV) and drive pathological remodeling. We hypothesized that intramyocardial delivery of a hydrogel within the MI region would lower wall stress and reduce adverse remodeling in Yorkshire pigs ( n  = 5). 99m Tc-Tetrofosmin SPECT imaging defined the location and geometry of induced MI and border regions in pigs, and in vivo and ex vivo contrast cine computed tomography (cineCT) quantified deformations of the LV myocardium. Serial in vivo cineCT imaging provided data in hearts from control pigs ( n  = 3) and data from pigs ( n  = 5) under baseline conditions before MI induction, post-MI day 3, post-MI day 7, and one hour after intramyocardial delivery of a hyaluronic acid (HA)-based hydrogel with shear-thinning and self-healing properties to the central infarct area. Isolated, excised hearts underwent similar cineCT imaging using an ex vivo perfused heart preparation with cyclic LV pressurization. Deformations were evaluated using nonlinear image registration of cineCT volumes between end-diastole (ED) and end-systole (ES), and 3D Lagrangian strains were calculated from the displacement gradients. Post-MI day 3, radial, circumferential, maximum principal, and shear strains were reduced within the MI region ( p  < 0.04) but were unchanged in normal regions ( p  > 0.6), and LV end diastolic volume (LV EDV) increased ( p  = 0.004), while ejection fraction (EF) and stroke volume (SV) decreased ( p  < 0.02). Post-MI day 7, radial strains in MI border zones increased ( p  = 0.04) and dilation of LV EDV continued ( p  = 0.052). There was a significant negative linear correlation between regional radial and maximum principal/shear strains and percent infarcted tissue in all hearts (R 2  > 0.47, p  < 0.004), indicating that cineCT strain measures could predict MI location and degree of injury. Post-hydrogel day 7 post-MI, LV EDV was significantly reduced ( p  = 0.009), EF increased ( p  = 0.048), and radial ( p  = 0.021), maximum principal ( p  = 0.051), and shear strain ( p  = 0.047) increased within regions bordering the infarct. A smaller strain improvement within the infarct and normal regions was also noted on average along with an improvement in SV in 4 out of 5 hearts. CineCT provides a reliable method to assess regional changes in strains post-MI and the therapeutic effects of intramyocardial hydrogel delivery. Graphical abstract: Unlabelled Image Highlights: Developed novel platform to assess left ventricle deformation in vivo and ex vivo. Local cardiac strains decreased progressively over 7 days in infarcted regions. Measured linear correlation between local degree of infarction and strain. Hydrogel injection improved strain in regions bordering the infarct. Hydrogel injection resulted in less ventricle dilation and larger ejection fraction.